2022
DOI: 10.26508/lsa.202101346
|View full text |Cite
|
Sign up to set email alerts
|

Rab40c regulates focal adhesions and PP6 activity by controlling ANKRD28 ubiquitylation

Abstract: Rab40c is a SOCS box–containing protein which binds Cullin5 to form a ubiquitin E3 ligase complex (Rab40c/CRL5) to regulate protein ubiquitylation. However, the exact functions of Rab40c remain to be determined, and what proteins are the targets of Rab40c-Cullin5–mediated ubiquitylation in mammalian cells are unknown. Here we showed that in migrating MDA-MB-231 cells Rab40c regulates focal adhesion’s number, size, and distribution. Mechanistically, we found that Rab40c binds the protein phosphatase 6 (PP6) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…An emerging function of PP6 is as a negative regulator of the Hippo signaling pathway (39, 40, 52). PP6 subunits interact with MOB1 in a phosphorylation-dependent manner (39, 40), and long-term depletion of ANKRD28 increased MOB1 T35 phosphorylation, regulating focal adhesion dynamics in cell migration (52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An emerging function of PP6 is as a negative regulator of the Hippo signaling pathway (39, 40, 52). PP6 subunits interact with MOB1 in a phosphorylation-dependent manner (39, 40), and long-term depletion of ANKRD28 increased MOB1 T35 phosphorylation, regulating focal adhesion dynamics in cell migration (52).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging function of PP6 is as a negative regulator of the Hippo signaling pathway (39, 40, 52). PP6 subunits interact with MOB1 in a phosphorylation-dependent manner (39, 40), and long-term depletion of ANKRD28 increased MOB1 T35 phosphorylation, regulating focal adhesion dynamics in cell migration (52). Our analysis revealed a significant increase in S9 and T35 MOB1 phosphorylation upon PP6c degradation, as well as an enrichment in the cellular component category for cell junctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the same authors found RAB40B to be highly expressed in more aggressive cancers, as well as in basal BC subtype. Additionally, RAB40C was found to regulate focal adhesion number, size, and distribution in migrating BC cells ( Han et al, 2022 ).…”
Section: Secretion/exocytosismentioning
confidence: 99%